Pandangan Mahasiswa UPI terhadap Peran Hukum Islam dalam Membentuk Keadilan Sosial di Indonesia: UPI Students' Views on the Role of Islamic Law in Shaping Social Justice in Indonesia - Rahma Fadhilah Yustya; Nabila Sheva Al-Muawanatusibjan; Wika Khoiratun Nisa; Jihan; Rahma Alfiyyah; Sri Ayu Novita Sari (Al-Faiza : Journal of Islamic Education Studies, 2026)
This study examines how students of Universitas Pendidikan Indonesia (UPI) view the role of Islamic law in supporting the creation of social justice in Indonesia, since their perspectives have not been widely explored in previous research. Using a descriptive quantitative approach, the study involved UPI students from various study programs who filled out an online questionnaire based on a Likert scale. The data collected were then processed through descriptive statistical analysis to identify general tendencies in students’ understanding and assessment of Islamic legal principles. The findings show that most students hold a positive view of Islamic law, particularly regarding its emphasis on justice, public benefit, and equality. They also consider Islamic law compatible with the Indonesian legal framework and see its values as relevant to social issues faced today. In general, students perceive Islamic law not only as a set of religious rules but also as a moral foundation that can contribute to efforts toward building a fairer society. These results indicate that UPI students recognize the potential of Islamic law to play a constructive role in strengthening social justice in Indonesia.